Collaborative Crisis Management in Controlling the Second Wave of Covid-19 - Agung Wicaksono; Ahmad Anwar; Muhammad Iqbal (Department of Political Science - Universitas Sains Al-Qur’an, 2022)
Covid-19 is a pandemic disease that has surpassed the global response capacity. At the beginning of the outbreak, numerous countries were unprepared to deal with the pandemic caused by the Covid-19 which has claimed numerous lives. As one of the world's most populous countries, Indonesia has been particularly hardly suffered by the Covid-19 pandemic. The worst-case scenario occured when Indonesia was struck by the Delta Variant's, a second Covid-19 wave. On the other hand, Indonesia has made significant progress in reducing the number of cases. Indonesia's government has invited all stakeholders from diverse backgrounds to work together to address the Covid-19 crisis. Indonesia has been demonstrating its rapid capability in overcoming the second wave. This paper examines how Collaborative Crisis Management has been used in Indonesia to control the pandemic.